“It’s Morbin’ Time”: The Morphology and Syntax of Morbius Memes - Mangiwet, Lander (Universitas Pendidikan Ganesha, 2024)
Memes are an everyday feature of the Internet nowadays, and recently they have become a point of interest in the field of linguistics. This study particularly has taken an interest in Morbius memes, a meme phenomenon replete with linguistic features, with the goal of unraveling the morphological and syntactic features that characterize them. The study is beneficial to the field of linguistics and memes. It provides students with examples of how to conduct scholarly work in the field of morphology and syntax, and it also serves as a preservation of meme culture. The study was conducted following a descriptive qualitative design that employed morphological and syntactic analysis. It abides by ethical standards: it does not infringe on the copyright of memes and ensures the results will be properly disseminated. The study found that the morphological regularities that characterize Morbius memes come in the form of word formation processes— namely clipping, backformation, compounding, blending, and derivation— and a feature the researcher refers to as “the -ing rule”. In the case of syntactic regularities, these come in the form of recurring and unique sentence constructions in which the “It’s morbin’ time” phrase is a constant feature. These linguistic features of Morbius memes are, as the researcher infers, an observable manifestation of linguistic creativity in which individuals are manipulating language for the purpose of creating memes. Furthermore, it goes to show that individuals subconsciously employ their innate linguistic knowledge in creating memes. Therefore, memes may serve as mediums for language practice.